Depression and Retinopathy in Patients With Type 2 Diabetes Mellitus: A Meta-Analysis. Issue 3 (April 2021) - Zou, Yaowu; You, Wenjun; Wang, Jing; Wang, Fei; Tian, Zhongyu; Lu, Jie; Sun, Weihong
Abstract : Supplemental digital content is available in the text. ABSTRACT: Objective: Patients with diabetes mellitus with comorbid depression are at an increased risk of macrovascular and microvascular complications. Studies have suggested a positive association between depression and diabetic retinopathy (DR), but the evidence has not been systematically summarized. Therefore, the aim of the study was to perform a meta-analysis to investigate the correlation of depression with DR in patients with type 2 diabetes mellitus. Methods: PubMed and EMBASE were searched for relevant studies through January 7, 2017. Fixed-effects and random-effects models were used to calculate overall odds ratio (OR) and confidence interval (CI). Subgroup analyses were conducted to examine whether the association was affected by adjustment for confounders or by age of study population. Results: A total of 11 cross-sectional and prospective cohort studies were included in the analyses, with 34, 185 individuals involved. Overall, patients with depression were at a significantly elevated risk of development of DR (fixed-effects OR = 1.50, 95% CI = 1.39–1.63; random-effects OR = 1.58, 95% CI = 1.35–1.84). The association did not vary by adjustment for confounders. However, a slightly larger pooled estimate was observed among studies with a mean age of <60 years (OR = 1.78, 95% CI = 1.46–2.07) than those with a mean age of ≥60 years (OR = 1.42, 95% CI = 1.16–1.75). Conclusions: Depression was significantly associated with an increased incidence of DR in patients with type 2 diabetes mellitus. However, the existing literature does not yet definitely document that whether depression contributes directly or indirectly to incident DR. Further prospective investigations identifying high-risk subgroups are warranted.